Introduction to Meta-Science in HRD. Issue 4 (November 2019) - Turner, John R.
The Problem: Research matters. Results from research can affect policy, practice, and future research. Taking every precaution to assure that research is conducted ethically, accurately, and correctly is a practice that should be exhibited by all disciplines. Unfortunately, this has not been the case with upward of 40% of published research identified as being nonreproducible. The Solution: The first step for any discipline is to be aware that meta-science problems exists and to identify necessary techniques for preventing these problems from occurring. The current Special Issue introduces meta-science to the field of human resource development (HRD) as a step in informing scholars and scholar-practitioners (a) about the potential problems that exists in other disciplines and (b) what steps could be taken to help prevent these problems from occurring in research within the field of HRD. The Stakeholders: HRD scholars and scholar-practitioners, collaborators of HRD, researchers, instructors, and students of HRD programs.